The Effect of Training Units of Varying Intensity on Some Motor Abilities of Junior Handball Goalkeepers - khanjer, alsajad; Mahmood , Mohammed (Journal of Physical Education, 2022)
The research aimed to prepare training units of varying intensity for handball goalkeepers, and to identify their impact on some of the motor abilities of handball goalkeepers. The researchers used the experimental approach by designing one group with a pre and post-test. The research subject was, (12) goalkeepers from Baghdad clubs (Aljaish, Alshorta and Alhashed). The data processed statistically by (SPSS). The researchers concluded that the used training units and their variability in terms of times and stress had a significant impact on the development of agility motor abilities, reaction speed and compatibility, and an emphasis on diversity in preparing exercises for goalkeepers to reach ideal performance.